Analisis Kolokasi Verba Bahasa Inggris Berbasis Korpus Dalam Novel “Five Feet Apart” - Krisnawati, Krisnawati (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This research aims to explain (1) the frequency of verb bases forming verb collocations in the novel